KORELASI ANTARA HASIL BELAJAR MATA PELAJARAN BAHASA ARAB DAN EKSTRAKURIKULER BACA TULIS AL-QUR’AN SISWA KELAS 5 MI MA’ARIF KLIWONAN WONOSOBO - Kusuma Dewi, Tharienna Dhesta; Sunarko, Asep; Hidayat , Muhtar Sofwan (Al Jabiri: Jurnal Ilmiah Studi Islam, 2024)
The purpose of this study was to determine the relationship between extracurricular activities of Reading and Writing the Qur'an with the learning outcomes of Arabic language subjects for grade 5 students at MI Ma'arif Kliwonan Wonosobo. Because, in the world of education, teachers and schools must work together to improve the quality of learning so that they can produce quality students. Judging from the importance of the Qur'an in everyday life, the teacher's task as an educator is not only to improve academic abilities, but also to guide and direct students so that they are able to use the Qur'an as a guideline in carrying out daily activities. This study uses a quantitative research approach where this study focuses more on investigating the relationship between variables and testing theories. Data analysis was carried out using data collection techniques, then analyzed, compared and combined to form a systematic, integrated, and complete study. The population in this study were all grade 5 students of MI Ma'arif Kliwonan with a total number of samples used, namely 20 students. The results of this study indicate that there is a significant correlation between the ability to read the Quran of grade 5 students in the BTQ extracurricular with learning outcomes in the Arabic subject of grade 5 students of MI Ma'arif Kliwonan Wonosobo with a significance value of r count of 0.6442, where the results are greater than the r table value both at a significance level of 5% (0.4438) and 1% (0.5614).